2022
DOI: 10.1128/jmbe.00268-21
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Student Engagement through Course Attributes, Community, and Classroom Technology: Lessons from the Pandemic

Abstract: While many STEM (science, technology, engineering, and mathematics) instructors returned to in-person instruction in fall 2021, others found themselves continuing to teach via online, hybrid, or hybrid flexible (i.e., hyflex) formats. Regardless of one’s instructional modality, the findings from our own and other studies provided insight into effective strategies for increasing student engagement and decreasing cognitive overload. As part of this perspective, we included data from undergraduate students, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The study's findings emphasize the importance of teaching presence in improving student engagement in online courses. This is consistent with previous studies that have shown the efficacy of interactive classroom environments and prompt feedback in online learning contexts [40,41,45,46]. Our study supports the significance of establishing interactive classroom environments, which aligns with previous research [40,41], highlighting the value of incorporating collaborative activities, group discussions, and peer interactions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study's findings emphasize the importance of teaching presence in improving student engagement in online courses. This is consistent with previous studies that have shown the efficacy of interactive classroom environments and prompt feedback in online learning contexts [40,41,45,46]. Our study supports the significance of establishing interactive classroom environments, which aligns with previous research [40,41], highlighting the value of incorporating collaborative activities, group discussions, and peer interactions.…”
Section: Discussionsupporting
confidence: 92%
“…Ref. [45] underscore the significance of delivering content in a clear and organized manner to enhance engagement, a claim that our research findings support. When instructors present course materials in an organized and coherent manner, it enhances students' understanding and ability to navigate the course, thereby reducing cognitive load and potential frustration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…One approach is to enhance students' sense of belonging by enrolling them into virtual learning communities, where they have increased opportunities to interact with classmates and more experienced peers (Pownall et al, 2022). Instructors can also create a sense of community both outside of and during online class meetings (Donham et al, 2022). For example, at the beginning of the semester, students can be asked to create profiles on their learning management system or on another online platform, where they upload pictures and share their interests outside of school.…”
Section: Teaching Implicationsmentioning
confidence: 99%
“…In accordance with the conditions described in this study, lecturers may record so that they can repeat it all the time. By being able to play the video several times and replay it, it can reduce cognitive load (Donham, 2022). In the thematic analysis of emotional engagement, it was found that indicators that often appeared in response to open questions were asked, namely interaction with friends (68.1%), interaction with lecturers (67%), feelings during lectures (49.3%), responses to switching to online learning (34.4%), free time (19.6%), interaction with family (7.4%), and interaction with faculty/university (5.9%).…”
Section: Cognitive Engagementmentioning
confidence: 99%